2013
DOI: 10.1016/j.bpj.2012.11.2983
|View full text |Cite
|
Sign up to set email alerts
|

Transport Dynamics in a Glutamate Transporter Homologue

Abstract: Glutamate transporters are integral membrane proteins that catalyze neurotransmitter uptake from the synaptic cleft into the cytoplasm of glial cells and neurons 1 . Their mechanism involves transitions between extracellular-(outward-) and intracellular-(inward-) facing conformations, whereby substrate binding sites become accessible to the opposite sides of the membrane 2 . This process has been proposed to entail trans-membrane movements of three discrete transport domains within a trimeric scaffold 3 . Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
95
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(110 citation statements)
references
References 31 publications
(55 reference statements)
15
95
0
Order By: Relevance
“…Whereas the key structural features of secondary active glutamate transport have been established (Akyuz et al, 2013;Crisman et al, 2009;Reyes et al, 2009;Shrivastava et al, 2008), structural and mechanistic details of anion permeation have been hitherto unknown. In this study, we used a combination of computational and experimental approaches to determine how this class of transporters mediates anion permeation through an aqueous conduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the key structural features of secondary active glutamate transport have been established (Akyuz et al, 2013;Crisman et al, 2009;Reyes et al, 2009;Shrivastava et al, 2008), structural and mechanistic details of anion permeation have been hitherto unknown. In this study, we used a combination of computational and experimental approaches to determine how this class of transporters mediates anion permeation through an aqueous conduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In Glt Ph , for example, HP2 appears to spontaneously close in the substrate-free state and, therefore, substrate may not serve as a catalyst of the transition. Studies using smFRET, in which the movements of the transport domain have been observed directly, consistently seem to suggest that the translocation of the substrate-loaded transport domain is the slowest step of the transport cycle (137,138). This feature may well be peculiar to Glt Ph , which is a homolog from a hyperthermophilic archaeon.…”
Section: The Dynamics Of Structural Transitionsmentioning
confidence: 91%
“…A homolog of glutamate transporters from Pyrococcus horikoshii, the sodium-aspartate symporter Glt Ph is a founding member of the group of transporters with an elevator transport mechanism (Figure 2c and Figure 5). Elevator-like movements of the transport domain in Glt Ph have been demonstrated crystallographically (132)(133), by EPR (134,135), and by single-molecule FRET (smFRET) spectroscopy, both in detergent and in liposomes (136)(137)(138). Homotrimeric Glt Ph is composed of a central trimeric scaffold and three peripheral transport domains.…”
Section: The Architecture Of Elevator Transportersmentioning
confidence: 98%
“…According to previous experiments on glutamate and aspartate transporters, the large-scale conformational changes of membrane transporters frequently fall in the timescale of seconds (47,48). Such slow molecular events therefore may escape the observing capability of all-atom equilibrium simulations that can only track the timescale of microseconds or perhaps milliseconds at most.…”
Section: No Significant Conformational Changes Observed In the Equilimentioning
confidence: 97%